Concept of Cultural Practices in the Context of Social and Cultural Activities Management - Olena Liseienko; Oksana Petinova; Tetiana Poplavska; Halyna Wright (Socio-Cultural Management Journal)
Introduction. In the modern scientific discourse, there is a growing scientific interest in the conceptualisation of cultural practices, and the importance of researching the phenomenon of established (traditional) and innovative cultural practices in various spheres of public life is emphasised. This article aims to study cultural practices as cultural phenomena of people’s socio-cultural existence and key factors in managing socio-cultural activities. Purpose and methods. The purpose of the article is to provide the general scientific methods of formal logic (deduction, induction, analogy, synthesis), the method of analysing the opinions of scientists from different countries on several aspects of the problem under discussion, as well as the socio-cultural method to define cultural practices as a socio-cultural phenomenon.